Pemanfaatan Media Komunikasi dan Sumber Informasi Wanita Tani dalam Menerapkan Pertanian Perkotaan - Andriani, Yulia; Kausar; Haura Versha, Raihani (JURNAL KOMUNIKATIO, 2025)
Urban farming is an activity that is currently widely carried out by people in urban areas. This is due to the limited agricultural land in urban areas. So that urban farming becomes an alternative for people in urban areas to carry out agricultural activities. Agricultural activities are usually identical to work done by men, but in urban farming, women can also do it. This is because urban farming can be carried out flexibly around people's homes by utilizing land or yards that are limited in size and can use other alternative media to be a container for carrying out urban farming. In the current era of digitalization, all human activities cannot be separated from the use of communication media. In carrying out urban farming, women farmers need media to communicate and sources of information that are considered accurate and reliable to support their urban farming activities. This research aims to identify the characteristics of women farmers, the use of communication media and information sources in implementing urban farming in Pekanbaru City. The research method used is a survey method. The research approach was carried out with an ex post facto analysis design. Data analysis used to answer all research objectives is descriptive from the results of the Likert scale. The results of the research show that activeness in groups is a characteristic that is generally possessed by women farmers. The use of communication media and information sources by women farmers in implementing urban farming is classified in the very good category with a score of 4.39. The highest score is on the media indicator used in communication. This shows that the use of communication media and information sources among women farmers in Pekanbaru City is good.